2014
DOI: 10.1007/s10554-014-0558-x
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural magnetic resonance imaging for image-guided catheter ablation of scar-related ventricular tachycardia

Abstract: To present and validate a highly automated MRI analysis workflow for image-guided catheter ablation of scar-related ventricular tachycardia (VT) ablation procedures. A cohort of 15 post-infarction patients underwent MRI prior to VT ablation. The MRI study included a black-blood turbo spin echo sequence for visualizing the aortic root and ostium of the left main (LM) coronary artery, and a 3D late gadolinium enhanced sequence for visualizing the LV anatomy and myocardial scar substrate. Semi-automated segmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, histologically, fibrosis patterns ranged from homogeneous to patchy and to diffuse, with decreasing accuracy of detection by CMR. Prior studies of ischemic VT in which CMR scar was compared with EAM showed a good but imperfect correlation, with a significant mismatch in up to 1 of 3 patients (3), and a rather modest correlation with Cohen k coefficients (ranging from 0.36 (23) to 0.7 (24)). Indeed, studies with CMR and EAM showed consistently high scar transmurality points with nearly preserved voltage (1,3,10,19), supporting the notion that bipolar amplitude and CMR-determined interstitial fibrosis are closely related but represent 2 nonidentical aspects of pathophysiologic scar remodeling.…”
Section: Rationale For Combining Structural and Functional Vt Substramentioning
confidence: 93%
“…However, histologically, fibrosis patterns ranged from homogeneous to patchy and to diffuse, with decreasing accuracy of detection by CMR. Prior studies of ischemic VT in which CMR scar was compared with EAM showed a good but imperfect correlation, with a significant mismatch in up to 1 of 3 patients (3), and a rather modest correlation with Cohen k coefficients (ranging from 0.36 (23) to 0.7 (24)). Indeed, studies with CMR and EAM showed consistently high scar transmurality points with nearly preserved voltage (1,3,10,19), supporting the notion that bipolar amplitude and CMR-determined interstitial fibrosis are closely related but represent 2 nonidentical aspects of pathophysiologic scar remodeling.…”
Section: Rationale For Combining Structural and Functional Vt Substramentioning
confidence: 93%
“…Similarly, noninvasive cardiac imaging has been also evolving, playing now a relevant role in the characterization of patients with VAs. For example, in patients with nonischemic cardiomyopathy (NICM), multimodality imaging can help in identifying the arrhythmogenic substrate and in characterizing the specific anatomical–functional components of the ventricular tachycardia (VT) circuits ( 2 , 3 , 6 9 ).…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%
“…In these patients, multimodality imaging can help to identify arrhythmogenic substrate and critical components of VT circuits, leading to decreased radiofrequency ablation time, total procedure time, and improved acute and long-term ablation success rates. [ 11 17 ] In contrast, the impact of pre-procedural imaging to guide VT ablation in NICM differs based on the underlying NICM aetiology. Pre-procedural imaging can visualise the presence of epicardial substrates and predict when epicardial mapping may be warranted.…”
Section: Value Of Pre-procedural Imaging and Image Integration To Guimentioning
confidence: 99%